PREPARASI DAN KARAKTERISASI MIKROKRISTALIN SELULOSA (MCC) BERBAHAN BAKU TANDAN KOSONG KELAPA SAWIT (TKKS) - Fepri Effendi; Rina Elvia; Hermansyah Amir (ALOTROP, 2018)
[PREPARATION AND CHARACTERIZATION OF MICROCRYSTALLINE CELLULOSE (MCC) MADE FROM EMPTY PALM OIL BUNCHES (TKKS)] Empty Palm bunches (TKKS) is solid waste from industrial processing of oil palm (Elaeis guineensis Jacq) that have a high cellulose content.  This research aims to synthesize Microcrystalline Cellulose (MCC) from TKKS and determine the characteristics of the MCC produced. The manufacturing process begins with the MCC delignifikasi multistage pulping TKKS using mixed of 3.5% HNO3 and NaNO2 in temperatures of 90 ?C for 2 hours, followed by heating of a mixture of 2% NaOH and Na2SO3 2 % at temperature 50?C for 2 hours. The second stage of the lignification process is done using NaOH 17.5 %, followed by hydrolysis towards ?-Cellulose lignification results with heating in the aqueous solution of HCl at concentrations of 3, 3.5 and 4 M for 30, 45 and 60 minutes. From the results obtained from the hydrolysis of the optimum yield of 80.73 %, i.e., MCC that use concentration of HCl 3 M for 30 minutes.  MCC produced then analyzed using FTIR, XRD, and PSA. FTIR absorption for MCC results showed an of waves number on a 3375.43 cm-1 and 2899,01cm-1, indicating the presence of hydroxyl OH and CH.The results of the analysis with the PSA suggests that MCC has generated a measure of particle diameter 0.5281 µm. Using XRD analysis results that MCC has a degree of crystallinity of 86,79 %. And the results of testing the content of carbohydrates in MCC produced shows levels of carbohydrates of 88.36 %.